370. EXTERNAL VALIDATION OF A NOMOGRAM PREDICTING CONDITIONAL SURVIVAL AFTER CURATIVE TREATMENT OF ESOPHAGEAL CANCER. (24th September 2022) - Schuring, Nannet; Donlon, NE; Hagens, ERC; Donohoe, CMD; van Berge Henegouwen, MI; Reynolds, JV; Gisbertz, SS
Abstract: To predict 5-year overall survival for esophageal cancer patients after neoadjuvant treatment followed by esophagectomy, recently a conditional survival nomogram was developed. This nomogram includes cN-stage, ypT-stage, ypN-stage, cardiac comorbidity, chyle leakage and pulmonary complications as independent predictors of survival. The aim of this study was to externally validate the conditional survival nomogram in a cohort of patients from another European high volume esophageal cancer center. We included consecutive patients with a resectable (cT1-4a, N0–3, M0) adeno- or squamous cell esophageal carcinoma between January 2004 and January 2016 who received neoadjuvant treatment followed by an esophagectomy in a tertiary referral center for esophageal cancer. Standard prognostic factors and nomogram specific data were collected. The discriminative ability of the nomogram for the prediction of 5-year overall survival was quantified by Harrell's C-statistics, directly after surgery and given survival for 1, 2, 3 and 4 years already survived. Calibration of the conditional survival nomogram was visualized by plotting actual 5 years survival against predicted probabilities. 296 patients were included. The median overall survival was 48.1 months (95%CI:37.5–58.7). The probability to achieve 5-year overall survival directly after surgery was 45% and increased to 57%, 68%, 78% and 89% for each additional year survived. Prediction of 5-year overall survival differed from the observed survival with a calibration slope of 0.54, 0.55, 0.59, 0.73 and 1.09, directly after surgery and given 1, 2, 3, and 4 years already survived, respectively. The discriminative ability of the nomogram for 5-year survival was moderate with a C-statistics of 0.65, compared to a value of 0.70 in the original study. This study externally validated a model for conditional survival after neoadjuvant chemoradiotherapy and surgery for esophageal cancer. The proposed nomogram had a moderate predictive discrimination and accuracy for the derivation cohort, and therefore it should be updated for or used with caution in external cohorts for the prediction of conditional 5-year survival.